Effect of vertical step height on boarding and alighting time of train passengers. (May 2016) - Holloway, Catherine; Thoreau, Roselle; Roan, Tyng-Rong; Boampong, Derrick; Clarke, Theresa; Watts, David; Tyler, Nick
New train stock or train services are continually being added to the network in the UK. Their design, in conjunction with European Regulations on train floor and rail height, means there is often a gap between train and platform necessitating at least one physical step. This paper presents the results from a series of experiments testing the time required to board or alight a train across three different gap heights. The experiments were designed to test for the effect of age and luggage type on the time to board or alight. As expected, more steps result in a longer time required to board or alight. More interesting is the effect of age and luggage on time to board and alight with younger people being relatively unaffected by the presence of steps and luggage, whereas both these factors hinder elderly people. The quantification of these effects has implications for accessibility of train services and for train dwell times and can be used by others in the design and planning stages of rail projects.